Modified Poly (Lactic Acid) (PLA) Filament For 3d Printing With Improved Thermal Properties - Rafie, Muhammad Akhmal Firdaus (Universiti Sains Malaysia, 2018)
In this research, the primary objective is to study the effect of plasticizers and annealing on mechanical and thermal properties of the PLA structure The blend of PLA with plasticizers namely Poly (ethylene glycol) (PEG) is prepared with different blend ratio 100/0, 95/5 and 90/10. Single screw extrusion has been used to blend the composition to produce the materials for compression moulding and filament for 3D printing. Different die diameter has been used to produce the filament. It was found that increasing the PEG content will decrease the tensile strength and tensile modulus with increase the elongation at break. This is due to the plasticizer effect which reduces the glass transition temperature (Tg) and impart flexibility to the PLA structure. For thermal properties, the DSC analysis shows the decrease of Tg and cold crystallization temperature (Tcc) results as the plasticizer level increased to enhanced chain mobility. XRD analysis shows the smaller peak detects at 10% PLA/PEG blends and other blends shows amorphous graph. To improve the properties, annealing process has been done at temperature of 70 0C, 90 0C and 120 0C for 90 minutes. For 3D printing, bed temperature has been used to study the heat transfer from one layer to another. For mechanical properties, results shows that annealing at 90 0C is the optimum temperature which increase the tensile strength, elongation at break and tensile modulus for annealing and 3D printing samples. For thermal properties, DSC analysis shows the decrease of Tg and Tm with formation of double melting peak result in melt-recrystallization occur. XRD analysis shows the peak detects at 2